Religion and human security: a global perspective - Lombardi, Clark B.; Wellman, James K. (Oxford University Press, 2012)
This volume of essays explores the long-unstudied relationship between religion and human security throughout the world. The essays show that religion can have positive as well as negative effects on human wellbeing